Elongation in the major direction of tobacco mosaic virus assembly - Fukuda, Megumi (1985)
Butler and Lomonossoff [Butler, P. J. G. & Lomonossoff, G. P. (1978) J. Mol. Biol. 126, 877-882] claim that the elongation in the major direction (3′→5′) proceeds by incorporation of disk protein in tobacco mosaic virus (TMV) assembly. The strongest argument they have for this theory is the periodicity of 50 or 100 nucleotides that they observed in the banding pattern of the protected RNAs during the first few minutes of the assembly reaction. We repeated their experiment using TMV-OM (a common Japanese strain) disk protein and TMV-OM RNA. We observed a banding pattern similar to theirs, but we found the long protected RNA at 6 min to be from the 260-nm intermediate particle rather than from the full-length TMV RNA. We also carried out the assembly reaction between TMV-OM disk protein, as well as cucumber green mottle mosaic virus (CGMMV) protein, and three strains of TMV RNAs. During the course of each assembly reaction, we examined the banding patterns. We demonstrated that the banding pattern of the protected RNA differs depending on what kind of RNA is used, rather than on what kind of aggregational state the protein is in. Specifically, the similar banding pattern observed for CGMMV subunit protein was also observed for TMV disk protein in the assembly reaction with TMV (OM) RNA. We showed previously that the assembly reaction between CGMMV protein and TMV RNA proceeds by incorporation of CGMMV subunit protein. This strongly indicates that the banding pattern of the protected RNA does not arise from the stepwise addition of the 20S disk protein.